The Effectiveness of Cognitive-Behavioral Stress Management on Relapse Prevention in Substance Dependent Men - Negar Karimian (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: The purpose of this study is to investigate the effectiveness of cognitive-behavioral stress management on relapse prevention in men who are substance dependent. Method: In a experimental study, 30 individuals who settled in Esfahan therapeutic community center were accidently divided in to an experimental (15 subjects) and a control (15 subjects) group. The experimental group underwent ten 90 minutes sessions of cognitive-behavioral stress management and the control group didn't receive any particular treatment. All participants underwent urine tests at the beginning of the study, completion of treatment and three months following the completion of treatment. Data were analyzed using descriptive statistics and X2 test. Findings: results showed significant difference in relapse rates of two groups in the following stage. Conclusion: Cognitive-behavioral stress management is effective in relapse prevention in men who are substance dependent.